THE INFLUENCE OF STOCK CHARACTERISTICS ON RETURN IN CONSUMER GOODS INDUSTRY COMPANIES - Ivan Alexander Nanlohy; Putu Anom Mahadwartha; Arif Herlambang (Journal of Management and Business, 2018)
This study aims to determine the influence of stock characteristics with stock returns on consumer goods industry companies listed on the Indonesian Stock Exchange period 2011- 2015. Stock characteristics are illiquidity, size, beta, risk and dividend yield. This study uses quantitative approach by using multiple linear regression method in the form of panel data. This study uses a sample of consumer goods industry companies listed on the Indonesia Stock Exchange period 2011-2015. The number of samples used in this study is 125 years of observation consisting of 25 companies. The finding of this study indicates that the influence of stock characteristics with stock returns. Illiquidity has no significant positive effect on stock return. Size has no significant positive effect on stock return. Beta has a significant positive effect on stock return. Risk has a significant negative effect on stock return. Dividend yield has a significant negative effect on stock return.